SYSTEMATIZATION OF APPROACHES TO THE RESEARCH OF THE CONCEPTUAL AND CATEGORICAL FRAMEWORK OF SUSTAINABLE DEVELOPMENT OF RURAL AREAS - Давидюк, Микола В. (Journal of Strategic Economic Research, 2024)
The article is devoted to the systematization of approaches to the research of the conceptual and categorical framework of sustainable development of rural areas. The role of rural areas is substantiated: as a basis for conducting agriculture and the well-being of the rural population; as a factor in the intensification of agricultural production and the basis for the implementation of one of the Sustainable Development Goals (End hunger) through ensuring food security; as an object of purposeful influence on the part of the state and the private sector and the foundation of national competitiveness. Modern legal and scientific approaches to the interpretation of the categories "rural areas", "sustainable development", "sustainable development of rural areas" have been studied and summarized. On the basis of the conducted analysis, the author’s definition of the concept of "rural areas" as a historically and naturally formed multifunctional system, which includes a geographical space with natural conditions and resources (material and immaterial), rural settlements in accordance with the administrative-territorial system (villages, hamlets and possibly small towns), where the overwhelming majority of the rural population lives, engaged in diversified economic activities (both agricultural and non-agricultural activities (for example, rural tourism, provision of some industrial and other services, etc.), communications, as well as relevant inter-village areas (those that are outside the boundaries of rural settlements, but do not belong to urban areas due to their agricultural purpose, historical significance, or other reasons). The structural components of rural areas are outlined. The essence of the sustainable development of rural areas is substantiated, a number of key problems of the sustainable development of the latter, deepened by military actions on the territory of our state, are singled out. The need to develop appropriate mechanisms and establish at the legislative level (as a law, not by-laws) an appropriate strategy for the sustainable development of rural areas was emphasized.